Vasovagal Syncope Following Pulsed Radiofrequency of Cervical Dorsal Root Ganglia and Occipital Nerves in a Patient with Chronic Cervical Radiculopathy and Occipital Neuralgia: A Case Report - Kurnia Hendra Wijaya; Buyung Hartiyo Laksono (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Pulsed radiofrequency is a minimally invasive, non-destructive neuromodulation technique used to manage chronic cervical radicular pain and occipital neuralgia. It is generally considered safe, with common adverse events limited to mild transient dysaesthesia or local discomfort. Vasovagal syncope following pulsed radiofrequency of the cervical dorsal root ganglia and occipital nerves has not been well documented in the anaesthesia and pain medicine literature. Case presentation: A 41-year-old woman with chronic cervical radiculopathy attributable to C5–C6 herniated disc disease, tension-type headache with pericranial tenderness, a history of cluster headache, chronic spontaneous vertigo, and newly diagnosed hypertension underwent bilateral pulsed radiofrequency of the lesser and greater occipital nerves and of the C3 and C4 dorsal root ganglia under fluoroscopic guidance. The procedure was performed under light sedation with intravenous propofol and midazolam and completed without immediate complication. Approximately 20 hours later, the patient developed an acute decrease in consciousness with a nadir Glasgow Coma Scale of 12 and a heart-rate profile consistent with a reflex vasovagal event. Gradual spontaneous recovery of consciousness was documented over seven hours, reaching a Glasgow Coma Scale of 15 without any neurological deficit. Pre- and post-procedural symptom comparison showed clear improvement in cervical paraesthesia, vertigo, tinnitus, and cluster-type headache, while tension-type headache persisted at a similar intensity. Conclusion: Vasovagal syncope is a rare but clinically relevant adverse event after pulsed radiofrequency of the cervical dorsal root ganglia and occipital nerves. The likely pathophysiology involves afferent stimulation of the trigeminocervical complex and activation of the Bezold–Jarisch reflex in a susceptible patient. Multimodal monitoring, adequate hydration, careful sedation titration, and structured post-procedural observation are recommended to anticipate and manage this complication.